2010
DOI: 10.1073/pnas.1010456108
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Saccharomyces cerevisiae capable of simultaneous cellobiose and xylose fermentation

Abstract: The use of plant biomass for biofuel production will require efficient utilization of the sugars in lignocellulose, primarily glucose and xylose. However, strains of Saccharomyces cerevisiae presently used in bioethanol production ferment glucose but not xylose. Yeasts engineered to ferment xylose do so slowly, and cannot utilize xylose until glucose is completely consumed. To overcome these bottlenecks, we engineered yeasts to coferment mixtures of xylose and cellobiose. In these yeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
315
1
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 446 publications
(334 citation statements)
references
References 33 publications
10
315
1
8
Order By: Relevance
“…It is possible to control cellulose hydrolysis to accumulate more cellobiose over glucose (Homma et al, 1993;Vanderghem et al, 2009;Kim and Day, 2010), and production of ethanol from cellobiose has been demonstrated using yeast strains heterologously expressing b-glucosidase (Vanrooyen et al, 2005;Gurgu et al, 2011). Also, cellobiose and xylose co-fermentation has been used to produce ethanol (Nakamura et al, 2008;Saitoh et al, 2010;Li et al, 2010;Ha et al, 2011). However, to the best of our knowledge, this is the first report to describe co-fermentation of cellobiose and xylose for lipid production.…”
Section: Lipid Production By L Starkeyi On Cellobiose Glucose or Xymentioning
confidence: 91%
See 1 more Smart Citation
“…It is possible to control cellulose hydrolysis to accumulate more cellobiose over glucose (Homma et al, 1993;Vanderghem et al, 2009;Kim and Day, 2010), and production of ethanol from cellobiose has been demonstrated using yeast strains heterologously expressing b-glucosidase (Vanrooyen et al, 2005;Gurgu et al, 2011). Also, cellobiose and xylose co-fermentation has been used to produce ethanol (Nakamura et al, 2008;Saitoh et al, 2010;Li et al, 2010;Ha et al, 2011). However, to the best of our knowledge, this is the first report to describe co-fermentation of cellobiose and xylose for lipid production.…”
Section: Lipid Production By L Starkeyi On Cellobiose Glucose or Xymentioning
confidence: 91%
“…For example, a S. cerevisiae strain displaying b-glucosidase on its cell surface co-fermented cellobiose and xylose (Nakamura et al, 2008;Saitoh et al, 2010). S. cerevisiae strains harboring a cellodextrin transporter and an intracellular b-glucosidase also metabolized cellobiose and xylose simultaneously (Li et al, 2010;Ha et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Cellulolytic fungi engineered as described here to enable cellodextrin induction of cellulases would lack the β-glucosidase enzymes required to produce glucose. However, recent studies using N. crassa cellodextrin transporters indicate organisms that ferment xylose and cellobiose simultaneously may perform better than those that ferment glucose and xylose sequentially (22,42). The combination of cellodextrin induction of cellulases in filamentous fungi with yeasts that can ferment cellodextrins may prove beneficial in developing an economical process of biofuel production from plant biomass.…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous metabolic engineering studies in which the metabolic network of an organism has been altered by the addition of NAD(P)H-dependent oxidoreductase(s), or pathways including them [100,[160][161][162][163][164]. One of the most frequent goals of this type of approach is the efficient production of a given chemical of interest without the need for chemical synthesis or purifying enzymes, and ideally from renewable feedstocks and with a lower energy consumption due to the mild conditions at which reactions can be catalyzed by NAD(P)H-dependent oxidoreductases.…”
Section: Metabolic Engineeringmentioning
confidence: 99%